Magnesium Sulfate and Fentanyl for Facilitating Awake Fiberoptic Nasotracheal Intubation: A Randomized Study - Dhiman, Shweta; Bhalotra, Anju Romina; Kumari, Ruchi; Sharma, Kavita Rani; Verma, Uttam Chand (Annals of Anesthesiology and Critical Care, 2019)
Background: Various drugs have been used to facilitate awake ﬁberoptic intubation (AFOI). Although fentanyl is probably used most frequently, magnesium sulfate can provide muscle relaxation without respiratory depression and attenuate hemodynamic responses. Methods: We randomly allocated 20 patients of both sexes, aged 18 - 60 years, and ASA status I-II to receive fentanyl 2 g/kg (group F) ormagnesiumsulfate 45mg/kg (groupM) before AFOI. The intubating conditionswere evaluated by Ramsay sedation score (RSS), cough score, post-intubation score, additional topicalization requirement, and hemodynamic response. Oxygen desaturation, airway morbidity, recall of procedure, and the patient’s willingness to return for the same kind of anesthesia, if required, were also studied. Statistical analyses were done using SPSS V. 17.0 software. Numerical data were analyzed using independent and paired t-tests and categorical data using the chi-square test. P values of < 0.05 were considered signiﬁcant. Results: RSS, cough score, post-intubation score, lignocaine dose, airway-related morbidity, and willingness to undergo the same kindof anesthesia for a secondtimewere comparablebetweenthe twogroups. Bothdrugshadcomparable eﬀectsonhemodynamic response to intubation. However, the incidence of recall of the procedure was signiﬁcantly lower in group F (P = 0.003). Conclusions: The degree of coughing during ﬁberoptic bronchoscopy, tolerance of the endotracheal tube after intubation, and the hemodynamic response to intubationwere similar after the administration of either fentanyl 2 g/kg ormagnesiumsulfate 45 mg/kg.